Pengembangan Pariwisata dengan Mendorong Ekonomi Kreatif Melalui Festival Balap Sampan Mini dan Inovasi Produk UKM Desa Paremas - Muhammad Ridwan Rafsanjani; Yulia Rahmah; Jazera Alfani; Erich Efendi Mahesa; Alamsyah Mustika Wardani; Imam Rustandi; Cok Istri Wulandari; Abdul Jihad; Muzalli Andrean; Ilham Kurniawan; Nurkomalasari Nurkomalasari; Tri Mei Elita; Anggia Muawwadatul Audini; Putri Martina Lianti; Saprizal Hadisaputra (Unram Journal of Community Service, 2021)
Paremas Village is one of the villages located in Jerowaru District, East Lombok Regency, West Nusa Tenggara Province. This village has a lot of potential for natural wealth and local cultural wisdom, but Paremas Village is still not widely known by the wider community. The tourism arrangement that is still lacking makes tourism in Paremas Village fairly unfeasible. Therefore, the purpose of the New Normal Era Thematic Community Service Program at the University of Mataram for the July-August 2021 period is to develop tourism in Paremas Village by developing tourism by encouraging the Creative Economy Industry through the Festival Balap Sampan Mini Desa Paremas and product innovation of Kerupuk Cangkang Kepiting. The methods used are survey, observation, practice, documentation, and promotion. The results obtained are the re-emergence of the community's spirit to preserve traditions and increase community creativity in producing sampan mini and innovate by adding variants of Kerupuk Cangkang Kepiting. By encouraging the development of the creative economy industry in Paremas Village, it is hoped that it can encourage the community to be more productive with every potential they have and improve the welfare of the community